Morphological and molecular characterization of Trichuris muris (Nematoda: Trichuridae): studies from two commensal rodent species - Panti May, Jesús Alonso (2023)
In this paper we re-describe Trichuris muris based on morphological data following isolation from two commensal rodent species, Mus musculus from Mexico and Rattus rattus from Argentina. Furthermore, we provide a molecular characterization based on mitochondrial (cytochrome c oxidase subunit 1 mitochondrial gene) and nuclear (internal transcribed spacer 2 region) markers in order to support the taxonomic identification of the studied specimens of T. muris from M. musculus. We distinguished T. muris from 29 species of Trichuris found in American rodents based on morphological and biometrical features, such as the presence of a spicular tube, length of spicule, size of proximal and distal cloacal tube and non-protrusive vulva. We suggest that spicular tube patterns can be used to classify Trichuris species in three groups. Considering that the diagnosis among the species of this genus is mainly based on morphometry, this proposal represents a relevant contribution. We provide molecular studies on two markers, making this the first contribution for T. muris in the Americas. This study makes an important contribution to the integrative taxonomy of cosmopolitan nematode species, and its correct determination from the parasitological study of commensal rodents.